Psychosocial Work Environment on Employee Performance through Work Stress at Samarinda Probation Centres Employees - Tamyis Ade Rama; Sri Mintarti; Sri Wahyuni (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Employee performance can be affected by all kinds of mental disorders that manifest as work stress due to the psychosocial work environment in which the employee is located. Therefore, the purpose of this study is to analyse the effect of psychosocial work environment on employee performance through work stress on employees of Samarinda Probation centre. This research was conducted by the census of all employees of the Samarinda Probation centre, as many as 40 employees. It collected data using a questionnaire that was analysed using the structural equation model method with the Partial Least Square approach through Smarts 3. The results showed that the psychosocial work environment has a positive and significant effect on work stress, the psychosocial work environment has a positive and significant effect on employee performance, the work stress has a positive and significant effect on employee performance, and the psychosocial work environment has a positive and significant effect on employee performance through work stress.